MAGIC ROUND: TEACHING MEDIA FOR COMPILING NEGATIVE SENTENCES - Tri Agustini Solihati; Gea Aristi (Indonesian EFL Journal, 2019)
Learning English is much harder for Indonesian students because of various aspects. Yet, the obstacles are able to overcome with any methods, strategies or media to achieve the goals of the teaching and learning process (Manan, 2017). This research focuses on developing teaching media, named Magic Round for teaching negative sentences. It was made to facilitate students in compiling grammatically correct sentences. This research was carried out by applying Research and Development (RD) which consists of several steps, including; preliminary studies, research planning, product design, product validation, product trial, and producing final product. The trial result in limited scale gained 81.67% from technology expert and 86.67% from material expert. Besides, the assessment of its usefulness, feasibility, and students’ responses toward the media reached 86.38%, 88.64%, and 87.18%, respectively. It means that Magic Round is valid and can be used without revision. In conclusion, Magic Round is appropriate to use in teaching English negative sentences.Keywords: magic round; negative sentences; research and development; teaching media; tenses.